2017
DOI: 10.1016/j.acap.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Refusal of Vitamin K by Parents of Newborns: A Survey of the Better Outcomes Through Research for Newborns Network

Abstract: Objective To survey newborn clinicians in the United States regarding the frequency of intramuscular (IM) vitamin K refusal by a parent, reasons for refusal, and approaches of clinicians to refusals. Methods An electronic survey was administered to the clinician site representative (nursery director or designee knowledgeable about site-specific nursery policies) at all newborn nurseries in the Better Outcomes through Research for Newborns (BORN) network of newborn nurseries. Results Of 92 BORN sites, 85 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
1
21
1
1
Order By: Relevance
“…13 Other than reports from single centers, there is a paucity of quantitative information about temporal changes in the frequency of refusal of intramuscular vitamin K, but there is a perception among clinicians that the frequency is increasing. 7 In a 2014 report from the National Center for Health Statistics, the percentage of outof-hospital births in the United States increased from 1.26% in 2011 to 1.36% in 2012, continuing an increase that began in 2004. 8 Among out-of-hospital births in the Parent' s perception that intramuscular vitamin K is not necessary (53%); parents desired natural birthing process (36%); concern about preservatives or ingredients (19%); concern about adverse reactions (14%); concern about harmful effect of pain for infant (11%); concern about dose being too high (11%); concern that injection causes cancer (8%); concern about potentially overwhelming infant' s immune system (1%)…”
Section: Frequency Of Intramuscular Vitamin Refusal By Parentsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Other than reports from single centers, there is a paucity of quantitative information about temporal changes in the frequency of refusal of intramuscular vitamin K, but there is a perception among clinicians that the frequency is increasing. 7 In a 2014 report from the National Center for Health Statistics, the percentage of outof-hospital births in the United States increased from 1.26% in 2011 to 1.36% in 2012, continuing an increase that began in 2004. 8 Among out-of-hospital births in the Parent' s perception that intramuscular vitamin K is not necessary (53%); parents desired natural birthing process (36%); concern about preservatives or ingredients (19%); concern about adverse reactions (14%); concern about harmful effect of pain for infant (11%); concern about dose being too high (11%); concern that injection causes cancer (8%); concern about potentially overwhelming infant' s immune system (1%)…”
Section: Frequency Of Intramuscular Vitamin Refusal By Parentsmentioning
confidence: 99%
“…We identified 9 original articles on reasons for intramuscular vitamin K refusal by parents. 3,4,7,8,[16][17][18][19] Details on data collection and results are shown in Table 1. There were 3 major categories of reasons for refusal of intramuscular vitamin K by parents of newborns.…”
Section: Reasons For Refusal Of Intramuscular Vitamin Kmentioning
confidence: 99%
See 1 more Smart Citation
“…28,45 Ensuring awareness of the serious risks appears essential, with researchers in a recent study from the United States finding that .69% of parents cited a lack of awareness of importance as a reason for vitamin K prophylaxis refusal. 46 Interestingly, there are also health professional factors associated with refusals of vitamin K prophylaxis. In a recent study in which researchers examined health professionals' attitudes toward vitamin K prophylaxis in New Zealand, it was found that 100% of the doctors surveyed thought vitamin K should be given to all infants, compared with 55% of the surveyed midwives.…”
Section: Latementioning
confidence: 99%
“…2,3 Despite this, rates of parental refusal of vitamin K for their newborn are on the rise. [4][5][6] The rationale behind parental vitamin K refusal is multifactorial and can include mistrust of the medical establishment. 7 This same sentiment is a major driving force behind the refusal of routine childhood vaccinations with studies revealing that parents who refuse IM vitamin K are more likely to refuse routine vaccinations and other forms of newborn prophylaxis such as the hepatitis B vaccine and erythromycin ointment for their child.…”
mentioning
confidence: 99%